Modifikasi Mesin Potong Rumput Model Gendong untuk Pemotong Pelepah Sawit - Darmanto, Seno; Firdaus, Ghifa; Suryana, Yusuf (Departemen Teknik Mesin, Fakultas Teknik, Universitas Diponegoro, 2020)
The process of modifying a lawn mower into a frond and fruit cutting machine is carried out through several stages including design drawings, component modification, assembly, and testing. Modification of components is done by making adapters from cylindrical iron, the connection of the handle and the holder of the handle. Cutting machine testing uses 2 types of cutting blades namely circular saw blade and chainsaw blades and is applied to cut the frond palm fruit. Based on the processing of test data, the circular saw blade saws one frond with an average time of 20.5 seconds, and cutting 175 palm fronds per hour and consumes 1.09 l/hour of fuel, while for chainsaw blades takes an average of 17.75 seconds, and trims 202 fronds/hour and consumes 1.26 l/hour of fuel